EFFECTIVENESS OF POP IMPLEMENTATION FOR POPULATION ADMINISTRATION SERVICES IN KADUNGORA DISTRICT: ANALYSIS OF CONFORMITY WITH NATIONAL STANDARDS - Riri Sawitri; Raden Imam Al Hafis (Yayasan Wayan Marwan Pulungan, 2026)
This study aims to evaluate the effectiveness of the implementation of Standard Operating Procedures (SOPs) for population administration services in Kadungora Subdistrict, Garut Regency, and to assess their compliance with national public service standards. The research questions focus on the extent to which SOPs are consistently implemented and the factors that influence service quality. The research uses a descriptive analytical qualitative approach, with data collection through in-depth interviews with subdistrict officials and the community, direct observation of the service process, and a literature review of 15 scientific references related to digitization, service innovation, and population administration service standards. Data analysis was conducted using an interactive model including reduction, presentation, and conclusion drawing. The results of the study show that SOPs have been adequately implemented, with procedures and costs that are in accordance with standards. However, there are limitations in the use of digitization, uneven service innovation, and transparency of service times. Recommendations for problem solving include optimizing public e-services, expanding proactive service innovation in all villages, and increasing transparency of service times. These findings provide relevant empirical insights for the development of more effective and responsive population administration services.